Experiences and challenges in the training of engineers during the Covid-19 pandemic - Díaz-Garay, Bertha Haydeé (2021)
Given that university education has been changing in response to the Covid-19 pandemic, this essay explores experiences and challenges (pedagogical, technological and administrative) associated with engineering education during the pandemic experience of 2020 and 2021. By focusing on three fundamental aspects -the technological virtualization of learning, resource management and the emotional impact of confinement- this essay discusses both regional and local experiences. Among other aspects, also addressed are realities such as the incipient technological mediation in our region, the limitations of resources for virtualization and access to connectivity, as well as the problems produced by confinement and the academic overload experienced by students. While the discussion remains open, we propose a space for teacher reflection on the post-pandemic nature of the professional training of engineers.